2012
DOI: 10.1002/j.1532-2149.2012.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture points are large fields: The fuzziness of acupuncture point localization by doctors in practice

Abstract: BackgroundAcupuncture textbooks, schools, practitioners and clinical researchers designing randomized controlled trials on acupuncture all assume that acupuncture points are small and must be located precisely.MethodSeventy‐one medical doctors with ≥200 h acupuncture training and ≥2 years of clinical experience independently identified 23 commonly used acupuncture points on a male volunteer, using sticky transparent films with an X/Y grid placed asymmetrically around acupuncture points.ResultsFor each acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Although these values were not representative for all acupoints because of the actual channel paths along the body surface and the variable inter-acupoint distance along channels, they provided estimations on how close the acupoints were on the body surface – as a matter of fact, some acupoints are indeed located closer than this distance. In combination with a previous study [29] showing that the location of acupoints by CM experts demonstrated variances in range 2.7 cm 2 to 41.4 cm 2 for their location, many ‘newly discovered’ acupoints after the Yellow Emperor’s Inner Classic could be mainly due to anatomical variations on the exact location of acupoints lying inside the same dermatome. In view of this, the investigation of the actual distance between dual acupoints over the BSA and its relationship with therapeutic characteristics of acupoints is necessary.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although these values were not representative for all acupoints because of the actual channel paths along the body surface and the variable inter-acupoint distance along channels, they provided estimations on how close the acupoints were on the body surface – as a matter of fact, some acupoints are indeed located closer than this distance. In combination with a previous study [29] showing that the location of acupoints by CM experts demonstrated variances in range 2.7 cm 2 to 41.4 cm 2 for their location, many ‘newly discovered’ acupoints after the Yellow Emperor’s Inner Classic could be mainly due to anatomical variations on the exact location of acupoints lying inside the same dermatome. In view of this, the investigation of the actual distance between dual acupoints over the BSA and its relationship with therapeutic characteristics of acupoints is necessary.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, a recent review considered the specificity of acupoints as controversial despite some scientific evidence [28]. Although acupoints were commonly considered as small cutaneous region, it was found a large variance on the skin surface area for the exact location of acupoints by CM experts [29]. This large variation may stimulate different skin loci – and possibly different dermatomes inducing unexpected or new therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, opinions on nonacupoints were controversial, especially the distance between nonacupoint and normal acupoint. Some researchers consider that acupoint is not located at a point on skin but in a field [ 14 ]; therefore the more proper name of acupoint is “acupuncture field” [ 15 ]. Moisberger recommend “a minimum distance of 6 cm between verum and sham points on face, hands and feet, and up to 12 cm for all other parts of the body” [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Locating the acupoint and the nonacupoint is rather arbitrary, and the surface area and spatial structure of an acupoint vary with the acupoint [39][41]. Thus, stimulating the nonacupoint and TE5 might have similar effects since these two points were close to each other, and the small difference in location might contribute to the differences in functional connectivity.…”
Section: Discussionmentioning
confidence: 99%